All-Russian physical education and sports complex «Ready to work and defense» as a level estimator of medical students’ professional competence in discipline «Physical education» - N. V. Sivas; V. V. Scherbakova; L. A. Varlamova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The problem of estimation of students’ professional competence level in “Physical education” is a difficult task to solve. The RWD complex corresponds the demands of the modern pedagogical evaluation and is the universal means of formation of quantitative evaluation of competencies. Analysis of the results shown by students in certain types of tests indicates a relatively weak preparedness for passing the standards of the RWD complex. To create the most favorable conditions for the formation of competence in the discipline “Physical education”  during the development of the educational program it is necessary to include types of the RWD complex among credit requirements and evaluate them in accordance with the score-rating system.